A hedonic approach to the effect of preferences for segregation in urban land prices in Bogota - Santana Viloria, Leonardo (Universidad de La Salle. Revistas. Equidad & Desarrollo., 2011)
The value of urban land is determined according to location and environment variables, as its price increases at the same rate that access to major roads, tradecenters and urban services increases. However, the pursuit of distinction, expressed as a preference for socio-economic segregation, is another variable that has an impact on this value. This paper aims to prove that this preference is a significant variable in determining the value of residential urban land, using the distance to the socioeconomic levels as a proxy variable of the preference for segregation, and estimating a hedonic model by using spatial econometric tools. It is found that there is indeed a significant connection between the value per square meter of urban land and the distance of a home to the different socioeconomic levels. The farther it is from levels 1, 2 and 3, and the closer it is to levels 4, 5 and 6, the higher the value per square meter of ground.